GARBHINI CHARDI (EMESIS GRAVIDARUM), ITS MANAGEMENT IN AYURVEDA - Jadhav, Shriniwas; K, Padmasaritha; Siddesh, Sunita (International Journal of Ayurveda and Pharma Research, 2015)
Acharya charaka has given specific importance to pregnant women and has compared them with oil filled vessel, which can be split by little displacement and to provide proper attention during pregnancy. Ayurvedic classics have mentioned Garbhini Chardi as one among the Vyakta garbha lakshanas, which can be correlated with emesis gravidarum. Emesis Gravidarum is a worldwide common obstetrical problem seen in the first trimester of pregnancy in about 50% of pregnant women.Nausea and vomiting tend to be worse in the morning termed Morning sickness, they frequently continue throughout the day. Vomiting in the early weeks of pregnancy is very common. If we do not correct the simple vomiting it leads to severe. So one should take care to treat this condition in initial stage and prevent complications. Different formulations and recipes have been mentioned in Ayurvedic classics which can easily be incorporated in day today life by a pregnant woman for Chardi. These are easy to prepare & easily available. Hence in this study an effort is made to list out simple & effective management of Garbhini Chardi with the help of various herbal preparations.